Earnings Management in Companies that Missed and Beat Analyst Consensus - Pratiwi, Ni Made Cesya; Wirama, Dewa Gede (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 16 No 1 (2021)DO - 10.24843/JIAB.2021.v16.i01.p04, 2020)
The aim of this study is to analyze the differences of earnings management between companies that missed and beat analyst consensus. Nonfinancial companies listed in the Indonesia Stock Exchange in 2017–2018 and have analyst consensus data available are used as the research sample, which consist of 28 companies observed for four quarters. The final sample in the analysis consists of 94 observations (firm-quarters). The independent sample t-test is used for data analysis. Results show that companies that missed analyst consensus have greater discretionary accrual than the group of companies that beat analyst consensus. Therefore, differences in earnings management between companies that missed and beat analyst consensus exist. Companies that missed analyst consensus are more inclined to conduct earnings management in the following period. This finding opens the possibility to develop a new hypothesis in the positive accounting research framework. Keywords: Analyst Consensus; Missed and Beat; Earnings Management.